Avaliação das lesões da cadeia ossicular da orelha média com a técnica de pós processamento das imagens tomográficas do osso temporal - Jebahi, Yasser (2016)
Introduction: Adequate preoperative evaluation is necessary for the surgical treatment of hearing loss in cases where ossicular chain injury is suspected. However, the anatomical details of the ossicular chain are not accurately identified by computed tomography. New methods of middle ear reconstruction may improve accuracy in this diagnosis. Objective: To evaluate the accuracy of the isotropic reconstruction of temporal bone tomography images in the diagnosis of ossicular chain pathology in comparison with the intraoperative findings. Methods: Forty-two patients with chronic otitis media or hearing loss underwent temporal bone tomography prior surgery and had their images evaluated by one radiologist. Eight anatomical structures of the middle ear ossicles were analyzed. The findings of the axial and coronal computed tomography, and post reconstruction images were compared to the intraoperative one. Validity and precision measurements of the two methods were calculated. Results: The concordance beetwen the surgeon and the radiologist were high in all variables , mainly in the manubrium of the hammer, long branch of the incus and incudostapedial joint. Regarding the precision in the diagnosis of the lesions, for the radiologist, there were high sensitivity with the reconstruction for the evaluation of the hammer manubrium (75,9%) and the long branch of the incus ( 61,5%). The specificity was also higher for the stapes ( 81,2%). Conclusion: The post-processing method improves the preoperative diagnostic of ossicular chain lesions, especially in regions of major importance in surgical rehabilitation (hammer manubrium, long branch of the incus, and stapes)